Influences of cognitive load on center of pressure trajectory of young male adults with excess weight during gait initiation - Kong, Lingyu; Zhang, Zhiqi; Bao, Jiawei; Zhu, Xinrui; Tan, Yong; Xia, Xihao; Zhang, Qiuxia; Hao, Yuefeng (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction: Falls and fall-related injuries in young male adults with excess weight are closely related to an increased cognitive load. Previous research mainly focuses on analyzing the postural control status of these populations performing cognitive tasks while stabilized walking progress but overlooked a specific period of walking known as gait initiation (GI). It is yet unknown the influences of cognitive load on this population’s postural control status during GI. Objective: This study aimed to determine the influences of cognitive load on the center of pressure (CoP) trajectory of young male adults with excess weight during GI. Design: A controlled laboratory study. Methods: Thirty-six male undergraduate students were recruited and divided into normal-weight, overweight, and obese groups based on their body mass index (BMI). Participants’ CoP parameters during GI under single and dual-task conditions were collected by two force platforms. A mixed ANOVA was utilized to detect significant differences. Results: Compared with the normal-weight group, the obese group showed significant changes in the duration and CoP parameters during sub-phases of GI, mainly reflecting prolonged duration, increased CoP path length, higher mediolateral CoP displacement amplitude, and decreased velocity of anteroposterior CoP displacement. During GI with 1-back task, significantly increased mediolateral CoP displacement amplitude occurred in the obese group. During GI with 2-back task, the obese group had increased CoP path length, higher mediolateral CoP displacement amplitude, as well as a decreased velocity of CoP displacement. Conclusions: Based on the changes in CoP parameters during GI with cognitive tasks, young male adults with excess weight, mainly obese ones, have compromised postural stability. During GI with a difficult cognitive task, obese young male adults are more susceptible to deterioration in their lateral postural balance. These findings indicate that the increased cognitive load could exacerbate obese young male adults' postural control difficulty during GI under dual-task conditions, putting them at a higher risk of experiencing incidents of falls. Based on these findings, we offer suggestions for therapists to intervene with these young male adults to ensure their safety of GI.